PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PREDIKSI PERMINTAAN EKSPOR INDONESIA DI PASAR GLOBAL TINJAUAN HUKUM DAN TEKNOLOGI SERTA KEBIJAKAN PERDAGANGAN - Juhana Nuryana; Annie Myranika; Rifqi Syifa’ul Qolbi; Muslimin; Hikmat Ansori (CV. Lafadz Jaya, 2026)
The development of Artificial Intelligence (AI) technology has opened new opportunities in analyzing and predicting export demand in the global market. This study aims to analyze the utilization of AI in predicting Indonesian export demand from legal, technological, and international trade policy perspectives. The research method used is normative legal research with a multidisciplinary approach that integrates legal, technological, and public policy analysis. The results show that the utilization of AI in predicting Indonesian export demand has significant potential to enhance export product competitiveness, optimize supply chains, and support trade policy decision-making. However, this implementation faces legal challenges related to data protection, intellectual property, algorithm regulation, and compliance with international trade agreements. This study recommends the formulation of a comprehensive regulatory framework that accommodates AI innovation while protecting national and consumer interests.